Through the looking-glass: Alice and Child Studies Multiple. (February 2020) - Sparrman, Anna
This is NOT an article about Alice in Wonderland. It is about the figure of Alice-the-child and an exploration of the contemporary theoretical research field of Child Studies. What if, I ask, Lewis Carroll's Alice had been one of the sources drawn upon when forming child research theories? The idea is to explore how the fictive child character Alice in Wonderland enacts key theoretical concepts in Child Studies. Out of this exploration grows the idea of Child Studies Multiple.